Huawei in North America: international corporate strategies under political pressures - Chapardar, Hadi; Wei, William (Henry Stewart Talks, 2021)
Huawei’s business in North America, 5G technology, Huawei/China & North America tension, Huawei’s actions in Canada, ICT, globalization and new complexities